Penyusunan Harga Pokok Produksi Menggunakan Process Costing Method (Studi pada Kelompok Budi Daya Udang): Preparation of Cost of Production Using Process Costing Method (Study on Shrimp Cultivation Group) - Yanto, Roni; Fazira, Nur (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2023)
Indonesia is a country that is developing the business world, one of which is in the industrial sector. The main thing for an industrial company to be a going concern is to increase the number of sales. Not all industrial companies can determine the cost of production correctly and precisely. In the science of cost accounting, there are many methods that can be applied in preparing the cost of manufactured, one of which is the process costing. This study found that were deficiencies that occurred in the object of research, namely the icaccuracy in allocating costs of production. This was caused by the lack of understanding of financial managers in determining the cost of production. The are several cost components that are not included so that the cost of production that is formed dose not represent or approach the real calculation. This occurs because managers consider that the cost component only formed when the company disburses funds/cash during the current period. The results of this study compare the preparation og the cost of production using the process costing method with the traditional method applied by the object of research.